Risk Indicators for Missing Teeth in Working-Age Pomeranians – An Evaluation of High-Risk Populations - Torsten Mundt, DDS; Christian Schwahn, PhD; Florian Mack, DDS, PhD; Ines Polzer, DDS (Blackwell Synergy, 2007)
The goal of this study was to examine whether psychosocial conditions for general health described in the public health literature are also reflected in tooth loss.